Comparative ontogenetic and transcriptomic analyses shed light on color pattern divergence in cichlid fishes. Issue 5 (15th August 2022) - Kratochwil, Claudius F.; Liang, Yipeng; Gerwin, Jan; Franchini, Paolo; Meyer, Axel
Abstract: Stripe patterns are a striking example for a repeatedly evolved color pattern. In the African adaptive radiations of cichlid fishes, stripes evolved several times independently. Previously, it has been suggested that regulatory evolution of a single gene, agouti‐related‐peptide 2 ( agrp2 ), explains the evolutionary lability of this trait. Here, using a comparative transcriptomic approach, we performed comparisons between (adult) striped and nonstriped cichlid fishes of representatives of Lake Victoria and the two major clades of Lake Malawi (mbuna and non‐mbuna lineage). We identify agrp2 to be differentially expressed across all pairwise comparisons, reaffirming its association with stripe pattern divergence. We therefore also provide evidence that agrp2 is associated with the loss of the nonstereotypic oblique stripe of Mylochromis mola . Complementary ontogenetic data give insights into the development of stripe patterns as well as vertical bar patterns that both develop postembryonically. Lastly, using the Lake Victoria species pair Haplochromis sauvagei and Pundamilia nyererei, we investigated the differences between melanic and non‐melanic regions to identify additional genes that contribute to the formation of stripes. Expression differences—that most importantly also do not include agrp2 —are surprisingly small. This suggests, at least in this species pair, that the stripe phenotype might be caused by a combination of more subtle transcriptomic differences or cellular changes without transcriptional correlates. In summary, our comprehensive analysis highlights the ontogenetic and adult transcriptomic differences between cichlids with different color patterns and serves as a basis for further investigation of the mechanistic underpinnings of their diversification. Abstract : The repeated evolution of the same traits in independent lineages is a fascinating phenomenon but the molecular causes are often unknown. Our work provides evidence that only a single gene, agouti‐related‐peptide 2, shows robust gene expression differences between African cichlid fish species that repeatedly evolved similarly looking stripe patterns. Highlights: A single gene,   agouti‐related‐peptide 2 ( agrp2 ), shows robust gene expression differences between African cichlid fish species that repeatedly evolved similar stripe patterns. Expression differences of agrp2 do not only associate with stereotypic patterns in cichlids, but also with the oblique stripe patterns found in some cichlids of Lake Malawi. Horizontal stripe patterns form postembryonically and, in most species, much later than vertical bar patterns. Spatial gene expression variation between pigmented and non‐pigmented regions of Lake Victoria cichlid bar and stripe patterns is subtle.